ANALISIS IMPLEMENTASI KEBIJAKAN DISTRIBUSI BBM BAGI NELAYAN MISKIN DI DESA LABUAN KABUPATEN TOJO UNA-UNA - Sandagang, Yoana Chendrakasih (Katalogis, 2013)
This research aims to analyze the policy implementation of fuel (BBM)distribution to the poor fishermen in Labuan Village, Tojo Una-Una Regency and factors inhibiting the implementation process using Mazmanian and Sabatier model (1983). The research useslikert instrument in wich data and information were analyzed by using descriptive-qualitative methode. The research results are: 1) the implementation process consiste of the information letter from Regency Leader, delivery policy output by socialization, and implemnted actions; 2) the implementation process have low efectivity; 3) The principal factor inhibiting implementation process associated with the nature of fisherman behavior that migt be difficult to change;Â 4) Several weaknesses in the policy contentsuch as: inconsistent objective, fund allocation, coordination, operating guideline, recruitment implementator condition, and the partnership made the implementation less efective to solve the problem; 5) This research also identify environmental factors which influence the implementation, they are: social condition, public support, constituency pressure, and high official commitment to incur their skill in order to solve the problem. Various weaknesses in the implementation process makes implementing the contrary due to the large gains in the black market. Policy implementation was not able to fight the market mechanism, fishermen used, black market occurs, which provide benefits to certain parties and in turn have an impact on fuel shortages for poor fishermen.Â